Pervasive fire danger continued under a negative emission scenario - Hyo-Jeong Kim; Jin-Soo Kim; Soon-Il An; Jongsoo Shin; Ji-Hoon Oh; Jong-Seong Kug (Nature Communications)
Abstract Enhanced fire-prone weather under greenhouse gas warming can significantly affect local and global carbon budgets from increased fire occurrence, influencing carbon-climate feedbacks. However, the extent to which changes in fire-prone weather and associated carbon emissions can be mitigated by negative emissions remains uncertain. Here, we analyze fire weather responses in CO2 removal climate model experiments and estimate their potential carbon emissions based on an observational relationship between fire weather and fire-induced CO2 emissions. The results highlight that enhanced fire danger under global warming cannot be restored instantaneously by CO2 reduction, mainly due to atmospheric dryness maintained by climatic inertia. The exacerbated fire danger is projected to contribute to extra CO2 emissions in 68% of global regions due to the hysteresis of climate responses to CO2 levels. These findings highlight that even under global cooling from negative emissions, increased fire activity may reinforce the fire-carbon-climate feedback loop and result in further socio-economic damage.